Analysis of the Halal Value Chain in a Globally Competitive Local Brand - Beik, Irfan Syauqi; Nurhayati, Immas; Ribowo, Sugeng; Richana, Nur (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Competitive advantage is a crucial value that companies must possess and integrate into their brand identity to succeed in market competition. This study analyzes the implementation of the halal value chain in Almaz Fried Chicken based on Porter’s theory using an exploratory qualitative approach, with data collected through interviews, observations, and documentation. The research focuses on how the halal value chain is applied at each stage, from production to after-sales service. The findings show that Almaz Fried Chicken, known by its slogan "The No. 1 Saudi Fried Chicken in Indonesia," has a competitive edge in every aspect of its supply chain, from raw material management to after-sales services. This advantage is further strengthened by a strong and consistent educational strategy tailored to the Indonesian market segment.